QUANTITATIF ANALYSIS OF THE 2013 CURRICULUM OF PHYSICS TEXT BOOK USING SCIENCE INSTRUMENTS TEXTBOOK RATING SYSTEM LABORATORY - Fatihah Suci S. A. J; Zeni Haryanto; Muliati Syam (UNIVERSITAS NEGERI MEDAN, 2020)
This study aims to: (1) describe the suitability of the textbooks for XI grade high school students in Physics under curriculum 2013 program based on the criteria that refer to STRS, spesifically at the aspects of laboratory activities (2) describe the quality of textbooks for XI grade high school students, curriculum 2013 based on the criteria that refer to STRS, specifically in laboratory aspects. This study is a descriptive study with an evaluative approach that describes the contents of the book. This study describes the quality of the Physics textbook for XI grade students curriculum 2013 published by a private or non-BSE at the aspect of laboratory activities. To collect the data, the researcher used the STRS modified by Septiana Karumaningrum as the instrument. The results of this study indicated that (1) this book has a suitability level of 78% based on the criteria that refer to STRS, spesifically in the aspects of laboratory activities. (2) this book has a good quality (B) based on the criteria that refer to STRS, spesifically in laboratory aspects